Analysis of Pension Fund Payment Data Processing Information System Design - Antari, Primadela; Bufra, Fanny Septiani; Andesti, Cyntia Lasmi (CV. Proaksara Global Transeduka, 2024)
Research has been carried out at PT. Pos Indonesia (Persero) Lubuk Sikaping, and problems were found regarding the processing of pension fund payment data, where data processing was still manual and data storage still used folders and stored in filing cabinets. The report creation process is long and inefficient. In writing this research using the SDLC development method (System Development life Cycle) using the Visual Basic 6.0 programming language. In the results of this research, the design analysis used is the Information System Flow. The results of this research are a new system that has the advantage of minimizing the risk of errors or errors error which occurs in processing pension fund payment data as well as assisting in preparing reports and archiving data. It is hoped that PT Pos Indonesia (Persero) Lubuk Sikaping can apply and use this new system and can overcome problems in processing data on pension fund payments.